Memory, forgetfulness and transcendence: dimensions of historicity in the Second untimely consideration. - Jiménez, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article presents a reflection on historicity in relation to the experience and consciousness of the temporal being, based on the analysis of said concept in Nietzsche’s Second untimely consideration. An attempt is made to describe and delimit each of the dimensions in which Nietzsche analysed the human experience of the history in search of an understanding of the historical and temporal experience of life. Therefore, it is necessary to previously understand the untimely nature of philosophical thought, as well as the role of forgetting as a creative power, fundamental for life. The present interpretation suggests the idea of philosophical thought as a synthesis of historical experience, of its dimensions and possible ways of assuming and living history. Such synthesis between what is forgotten, what is remembered and what transcends historical experience constitutes, consequently, the proper character of philosophy as a particular way of living.